(Landscape monitoring and assessment in Sirte (Libya - Mohammed, Hussein Ahmed; Habib, Badria Mohammed Omar Bakr (Journal of natural sciences, life and applied sciences, 2017)
Changing ecological and socio-economic circumstances make land degradation a major concern in Mediterranean area. The objectives were to examine the spatiotemporal patterns of land use/cover dynamics and quantify the rate and direction of these dynamics in Sirte, Libya. Remotely sensed data including Land cover (MCD12Q1), MODIS NDVI (MOD13A3) for 2001-2014 and TRIMM precipitation data for 2001-2014 were interpreted. The results showed no significant trend; but a decrease in sand dunes and semi-fixed sand dunes with a change rate of 15.66 and 116.37 km² year−1, respectively, in the meantime the vegetation cover has increased with an increasing rate of 112 km² year−1. The results also showed that the high-, and medium degree desertiﬁcation area has decreased by about (25 %) but showed no significant changes. However, land desertification monitoring and Assessment using remote sensing still needs to be continued and also refined for the purpose of long-term monitoring and the management of fragile environments in the area.
Keywords: landscapes; desertification; remote sensing; Sirte; Libya